Comparison of Clinical and Radiological Outcome Between Minimally Invasive Plate Osteosynthesis and Open Reduction and Internal Fixation in Distal Tibial Fractures (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To compare the clinical and radiological outcome between minimally invasive plate osteosynthesis and open reduction and internal fixation in distal tibial fractures.Methods:  This randomized controlled trial study was conducted in the department of Orthopedics, Sir Ganga Ram Hospital, Lahore from September from September 2013 to March 2015. Forty patients presenting with closed, displaced, distal tibial fractures without ankle involvement were divided into two groups using lottery method. Group-A underwent ORIF and Group-B underwent MIPO. A written informed consent was taken from every patient.Results: The mean age of the patients was 42.45±8.25 years in Group-A and 41.35±9.56 years in Group-B (p=.699). There were 13 (65%) male and 7 (35%) female patients in Group-A and 14 (70%) male and 6 (30%) female patients in Group-B (p=.736). Mean operative time was insignificantly higher in Group-B (73.90±5.15 vs. 70.75±6.10 minutes; p=.086) as compared to Group-A. Mean VAS score for post-operative pain (6.40±1.05 vs. 4.45±.95; p=.000) and mean length of hospital stay (4.35±1.04 vs. 2.70±.73 days; p=.000) was significantly higher in Group-A as compared to Group-B. 6 patients in Group-A developed flap necrosis compared to none in Group-B (30% vs. 0%; p=.008). 5 Patients in Group-A developed wound infection in 2nd post-operative week compared to only 1 patient in Group-B (25% vs. 5%; p=.077). On 12th post-operative week, radiological union was evident in all the patients (100%) of Group-B compared to 16 patients (80%) of Group-A, and this difference was statistically significant (p=.035).Conclusion: Though associated with insignificantly longer operative time, MIPO is associated with significantly decreased post-operative pain and length of hospital stay. MIPO offers the advantage of soft tissue protection thus minimizing infection